Effects of maternal iodine nutritional status on neurodevelopmental and cognitive function of rat offspring - Fu, Min; Wu, Wen; Guo, Wenxing; Jin, Qi; Meng, Qi; Gao, Yuanpeng; Yang, Rui; Yang, Ying; Wang, Zihao; Zhang, Wanqi (Frontiers in Nutrition, 2022)
Objectives This study aimed to explore the effect of maternal iodine status on the brain development of offspring in rats. Since in human studies, the interference of environmental factors and other nutrients cannot be removed. Materials and methods A total of 48 female Wistar rats were randomly divided into four groups: low iodine (LI), normal iodine (NI), 10-fold high iodine (10HI), and 50-fold high iodine (50HI). The rats were killed on the 15th day of pregnancy and lactation after collecting 24-h urine. The iodine concentration in 24-h urine, blood, and placenta of pregnant rats, and 24-h urine, milk, blood, and mammary glands of lactating rats was determined by inductively coupled plasma mass spectrometry. The thyroid hormone of pregnant and lactating rats was detected by chemiluminescence. The offspring were subjected to the Morris water maze on the 10th day after birth. Serum was collected to detect the thyroid hormone of offspring. The protein expression of neuroendocrine-specific protein (NSP)-A and brain-derived neurotrophic factor (BDNF) in the offspring brain were studied. Results Iodine storage in the placenta during pregnancy and mammary glands during lactation was positively correlated with iodine intake, and iodine storage in the placenta and mammary glands in the 50HI group was significantly higher than that in the NI group (P = 0.045 and P = 0.040). Compared with the NI group, the offspring thyroid-stimulating hormone (TSH) level was significantly higher in the 10HI group (P = 0.046), and the FT4 level was significantly lower in the 50HI group (P = 0.032). The Morris water maze showed that LI and 50HI groups required longer time and distance to find the platform than the NI group (P < 0.001). The platform crossing numbers in the LI and 50HI groups decreased significantly (P < 0.001). The expression of NSP-A in offspring brain was lower in the 10HI and 50HI groups than in the NI group (P = 0.026 and P = 0,008). BDNF expression levels were significantly lower in the LI, 10HI, and 50HI groups than in the NI group (P < 0.001). Conclusion Maternal iodine intake affects iodine storage in the placenta and lactating mammary gland, which in turn affects thyroid function and BDNF and NSP-A expression in the offspring.